(untitled) (GEOmedia, 2009)
GIS in action at the ESRI Italian Users Conference Different format and different location, but the ESRI Italian Users Conference still remain one of the biggest events in the GIS and Geographic Information italian sector. Beside the several technological issues and the project presentations, the 2009 edition allowed the first direct contact with ESRI Italia new management and has been the occasion for the announcement of the ESRI EMEA Conference, that will be held next year in Rome as well.